Pengaruh Prosedur Manajemeen Sumber Daya Manusia Terhadap Kinerja Pekerja Di Era Digital - Frizcha Affrillya Laffaysza; Riya Titi Kususmadewi; Nazwa Na’imatus Sahira; Rafika Meilia Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of human resource management (HRM) procedures on employee performance in the digital era. Developments in information technology such as artificial intelligence, big data, and digital systems have driven a transformation in HRM practices, shifting from primarily administrative to more strategic and technology-based. This study used a quantitative approach with explanatory research methods to examine the relationship between HRM procedures as the independent variable and employee performance as the dependent variable. The results indicate that digital-based HRM procedures have a positive and significant impact on employee performance. This is evident in the increased effectiveness of digital recruitment, the quality of e-learning-based training, the objectivity of digital performance assessments, and the efficiency of internal communication through digital platforms. Furthermore, employee performance in the digital era is measured not only by work output but also by technological adaptability, collaboration, and work flexibility. These findings confirm that digitizing HRM procedures can improve employee productivity, efficiency, and work quality. However, the success of digitalization implementation is greatly influenced by organizational readiness, employee digital competence, leadership support, and an adaptive organizational culture. Therefore, organizations need to optimize the use of technology in every HRM process to sustainably improve employee performance in the digital era.